PENERAPAN IJARAH DAN RAHN DALAM TRANSAKSI EKONOMI SYARIAH: PERSPEKTIF AYAT DAN HADITS - Dwi Bagus Priyanto,; Putri Ayu Fatma,; Nur Sa`adah Mahfudah, (Muadalah : Jurnal Hukum, 2025)
This article analyzes and compares the laws of Ijarah and Rahn in the perspective of Islamic fiqh, as well as their application in modern Islamic economic transactions. Using qualitative methods and literature study, this article shows the differences and similarities between Ijarah and Rahn, as well as the application for Islamic economic practices. The results of this study provide an overview of the application of Ijarah and Rahn in modern Islamic economics and provide an understanding of ijarah and rahn. This article can help improve the understanding and application of Ijarah and Rahn in Islamic economic transactions, as well as provide references for Islamic economic practitioners and researchers. Thus, this research can be a contribution to the development of Islamic economics in Indonesia